The Influence Of Mung Bean Extract Therapy And Avocado Juice On Reducing Cholesterol Levels In Hypercholesterolemia Patients In RT 003 RW 005, Pondok Benda Subdistrict, South Tangerang - Faizah, Rahma; Susanti, Dewi; Dinaryanti, Ratna Sari (Jurnal EduHealth, 2024)
Hypercholesterolemia is an increase in cholesterol levels in the blood, exceeding the normal limit, which is ≥ 200 mg/dl. If left untreated, it can lead to coronary heart disease, stroke, hypertension, and diabetes mellitus. The management of hypercholesterolemia can be done in two ways: pharmacological and non-pharmacological therapy. One non-pharmacological therapy that can reduce cholesterol levels is the consumption of mung bean extract and avocado. This study aims to determine the effect of mung bean extract therapy and avocado juice on reducing cholesterol levels in hypercholesterolemia patients in RT 003 RW 005, Pondok Benda Subdistrict, South Tangerang. The research design used a quasi-experimental method with a pretest-posttest non-equivalent control group design. The population in this study consisted of hypercholesterolemia patients, with a total sample of 26 respondents. The sampling technique used was probability sampling. The statistical tests used were the paired T-test and independent T-test. The results of the study showed that there was an effect of giving mung bean extract with a p-value = 0.001 (p<0.05), there was an effect of giving avocado juice with a p-value = 0.001 (p<0.05), and there was no difference between the administration of mung bean extract and avocado juice with a p-value = 0.925 (p>0.05) on reducing cholesterol levels in hypercholesterolemia patients. The results of this study are expected to serve as independent nursing interventions in providing complementary therapy to reduce cholesterol levels in hypercholesterolemia patients.